RANCANG BANGUN PENGAMAN MATA DENGAN LAYAR TV BERBASIS ARDUINO UNO - Andy Nugroho Prio Utomo; Edy Kurniawan; Muh Muhsin (KOMPUTEK, 2021)
Television is an electronic device which now the majority is owned by all Indonesians. Besides the use of this electronic device, there is a negative impact or thing that is contained in this electronic device. When watching television, eyes often experience tired and dry eyes, this is caused by television monitors that emit radiation rays and cause several eye problems. The radiation beam emitted from each television differs depending on the size of the monitor. This has been proven by tests that have been carried out by related institutions that the distance to watch television for each monitor is different. "The eye has the most important role for the development of human intelligence". Therefore a tool was designed from the problems that arise which will set the ideal distance for watching television using the PIR sensor to determine the distance of the audience from the television which will be forwarded to Arduino UNO as data processing, the output of the tool is in the form of LED, Buzzer and executed by Rellay as Automatic shutdown where the television will be turned off automatically when the audience enters a distance of less than 3 meters and within 1 minute with the LCD indicator displaying text data in the form of "Danger" and the television will not be turned off automatically if the viewing distance is more than 3 meters and the LCD will display text data in the form of "SAFE".